Preparation method of polypropylene diaphragm with uniform air permeability and porosity

By using a heating and cooling back-up air knife to accurately control the polypropylene melt in dry diaphragm preparation, the problem of uneven crystallization of cast base membrane is solved, the uniformity of breathable value and porosity is achieved, and the safety and stability of the diaphragm are improved.

CN119610740AInactive Publication Date: 2025-03-14康辉南通新材料科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510154850.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing dry diaphragm preparation technology, the cast base film has uneven crystallization due to temperature differences, which affects the uniformity of porosity and breathability value, and thus affects the safety and stability of the diaphragm.

Method used

The polypropylene melt is accurately controlled by a heating and cooling back-up air knife to ensure that the AK surface and CR surface crystallize simultaneously to form a parallel plate crystal structure. Through annealing, cold drawing, hot drawing and shaping processes, a polypropylene membrane with uniform breathability and porosity is produced.

Benefits of technology

By accurately controlling the diaphragm temperature, improving the crystallization behavior, improving the regularity and orientation of the diaphragm structure, significantly improving the uniformity of breathable value and porosity, reducing the defect rate of sagging and blasting ribs, and improving the safety and stability of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610740A_ABST
    Figure CN119610740A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a polypropylene diaphragm with uniform air permeability and porosity, and belongs to the technical field of lithium battery diaphragm production. Polypropylene is melted and plasticized by an extruder to obtain a polypropylene melt, and the polypropylene melt is extruded from a die head to form a molten sheet; controlling the temperature of the molten sheet to be 131-138 DEG C, enabling the molten sheet to enter a casting roller for tape casting, sequentially passing through a self-exhaust pressure roller and a cooling roller to obtain a polypropylene base film, and sequentially performing annealing treatment, cold drawing, hot drawing and shaping on the polypropylene base film to obtain the polypropylene diaphragm with uniform air permeability and porosity. Accurately controlling the temperature of the molten sheet to 131-138 DEG C by adopting a heating and cooling overstocked air knife; when the heating and cooling accumulation air knife is used for molding the melt, the AK surface is subjected to accurate temperature control, and the AK surface and the CR surface can be crystallized synchronously, so that the molten sheet has a parallel lamellar crystal structure and is highly oriented, and the air permeability value and porosity uniformity of the diaphragm are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery diaphragms and relates to a method for preparing a polypropylene diaphragm with uniform air permeability and porosity. Background Art

[0002] The diaphragm in lithium-ion batteries is the part with the highest technical barriers among the four major materials, and its cost is second only to the positive electrode material. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting, and it also has the function of allowing electrolyte ions to pass through. Among them, dry-process diaphragm products in energy storage mainly include single-layer PP, PP+ceramic coating, double-layer PP / PE, double-layer PP / PP, three-layer PP / PP / PP and three-layer PP / PE / PP, etc., which are mainly used in consumer batteries, power batteries and energy storage batteries, among which power batteries have received widespread attention due to their high safety.

[0003] With the rapid increase in demand for power batteries, higher requirements are placed on the safety of lithium-ion power batteries, and one of the key factors affecting the safety of lithium-ion power batteries is the safety of the diaphragm. Among them, the uneven porosity of the diaphragm directly affects the fluctuation of the battery's internal resistance. As the battery continues to discharge, the area with large internal resistance will increase the body temperature over time. When the diaphragm reaches the closed-pore temperature, some pores are too large to close and heal themselves, and the periphery of the micropores begins to shrink, making the pores larger and larger over time. When the micropore diameter is larger than the electron diameter, a short circuit between the positive and negative electrodes occurs, causing the battery to short-circuit, catch fire, or even explode. Therefore, improving the uniformity of the diaphragm pores will become the mainstream of the current battery market.

[0004] At present, in the preparation of dry-process diaphragms, for example, patent CN201110047740.7 records that a low-crystallinity, highly oriented polypropylene film is prepared by producing hard elastic fibers. The so-called hard elastic fibers are made by extruding a polypropylene melt from a die, and allowing the extruded melt to flow naturally down to a cooling roller (casting roller). One side of the flowing sheet melt adheres to the roller and is stretched at high speed to allow the melt to crystallize under a higher stress field. Then, heat-treated at a temperature 30°C to 40°C below the melting point, a hard elastic fiber having a lamellar structure arranged perpendicular to the extrusion direction and arranged in parallel can be obtained, and then annealed at high temperature to obtain an oriented cast base film with high crystallinity. Finally, the prepared hard elastic polypropylene cast base film is first stretched at low temperature to form micro-defects such as silver streaks, and then the defects are pulled apart at high temperature to form micropores.

[0005] The uniformity and orientation of the lamellae directly affect the uniformity and stability of the base film performance, which is the key to subsequent pore formation, and affects the size and density of the pores, directly affecting key indicators such as porosity, air permeability, tensile strength, and puncture strength. However, the process in patent CN201110047740.7 has the following defects: Since the cast base film is in contact with the heated roller surface on one side, there is a large temperature difference between the CR surface (melt and roller contact surface, roller surface temperature 100±10℃) and the AK surface (melt and air contact surface, ambient temperature 25±5℃), and with the fluctuation of ambient temperature, the AK surface crystallizes too quickly, the crystallization time difference of the lamellae on both sides of the membrane is too large, the lamellae arrangement fluctuates, the crystal orientation in the same direction is reduced, the regularity of the crystal arrangement is reduced, and the consistency of the arrangement direction is reduced. Due to the uneven molecular arrangement, the tensile force perpendicular to the extrusion direction is greatly different, which directly affects the pore size and uniformity of the cast base film perpendicular to the extrusion direction when the cast base film is stretched longitudinally. Also, due to the rapid cooling and crystallization of the polypropylene melt, single crystals cannot be obtained, but a spherulite structure is formed. The spherulite structure is relatively stable and not prone to defects. The working principle of patent CN201110047740.7 is to use the separation of lamellar crystals to produce defects, and then amplify the defects to make the required microporous membrane. Therefore, when the cold-drawn membrane silver lines appear, the membrane breaks or partially has no stretching defects, resulting in uneven micropores in the stretching process, large differences in pore size, and even the phenomenon of no pores, which has a great impact on the air permeability, porosity uniformity, safety, consistency and stability of the diaphragm product.

[0006] In order to solve the above problems, the existing technology usually adds an insulation plate to the casting roller for insulation or installs a fixed air knife. However, these two methods cannot adjust the temperature and wind line angle, and cannot provide temperature feedback, resulting in the inability to accurately obtain the environment required for crystal growth and ensure temperature consistency. Therefore, the temperature difference between the CR (roller) surface and the AK (air) surface exists for a long time.

[0007] Therefore, it is of great significance to study a method for preparing a polypropylene diaphragm with uniform air permeability and porosity to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing a polypropylene diaphragm with uniform air permeability and porosity.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity, wherein polypropylene is melted and plasticized by an extruder to obtain a polypropylene melt, the polypropylene melt is extruded from a die head to form a molten sheet, the temperature of the molten sheet is controlled at 131-138° C. to enter a casting roller for casting, and then the molten sheet is sequentially passed through a self-exhaust pressure roller and a cooling roller to obtain a polypropylene base film, and the polypropylene base film is sequentially subjected to annealing treatment, cold drawing, hot drawing, and shaping to obtain a polypropylene diaphragm with uniform air permeability and porosity;

[0011] The heating and cooling compressed air knife is used to accurately control the temperature of the molten sheet to 131~138℃;

[0012] The heating and cooling backlog air knife includes a ceramic heater, an anti-microwave infrared temperature sensor, an air inlet guide slot, a tubular heater, an air filter, a backlog box, a throttle valve, a fan, a servo motor, an air inlet filter and an air outlet chamber;

[0013] The air outlet cavity is a hollow structure with one end sealed and the other end open; the interior of the air outlet cavity includes a guide section and a non-guide section; the guide section is close to the sealed end of the air outlet cavity and is a vortex structure; the non-guide section is far away from the sealed end of the air outlet cavity, and a ceramic heater is arranged on the non-guide section to heat the airflow;

[0014] Above the die head is a die head bracket, the die head is hoisted on the die head bracket, and both sides of the air outlet chamber are installed on the die head bracket; the inner cavity of the air intake filter is connected to the air inlet of the fan, and the fan is connected to the servo motor. The air intake volume is adjusted by controlling the speed of the servo motor. The fan is also connected to the backlog box through a pipeline, and a throttle valve is arranged on the pipeline; the backlog box is connected to the air filter and the tubular heater in sequence, and the tubular heater is connected to the guide section through the air intake guide groove. The vortex structure of the guide section is designed to allow the airflow to be fully mixed in the guide section, making the temperature more uniform; the connection between the air intake guide groove and the guide section is set as the air inlet, the open end of the air outlet chamber is set as the air outlet, and the microwave-resistant infrared temperature sensor is installed at the air outlet for non-contact temperature measurement of the molten sheet.

[0015] The molten sheet flows out from the die head onto the casting roller. The heating, cooling and backlog air knife is in a non-contact state with the casting roller. The temperature is accurately measured by an anti-microwave infrared temperature sensor. According to the temperature comparison result, the ceramic heater and tubular heater are started / stopped respectively. At the same time, the casting roller cooperates with the heating, cooling and backlog air knife to slowly cool the molten sheet (hereinafter referred to as the membrane). The self-exhaust pressure roller is installed under the casting roller, and the membrane is passed between the self-exhaust pressure roller and the casting roller. After the membrane is flat, it is pressed on the self-exhaust pressure roller and then passed through the cooling roller to obtain a polypropylene base film. The polypropylene base film is successively cold-drawn, hot-drawn and shaped to obtain a polypropylene diaphragm with uniform air permeability and porosity.

[0016] When the heating and cooling backlog air knife is started, the servo motor is powered on, and the condition of the molten sheet is observed at the same time (standard: no surface defects such as holes are visually observed, and the edges are consistent), the distance and angle of the air outlet cavity are adjusted, and then the temperature is adjusted according to the actual temperature measured by the anti-microwave infrared temperature sensor on the molten sheet (the set temperature satisfies 131℃≤T≤138℃, which is synchronized with the actual temperature), and then the air permeability value, porosity and other indicators measured in the laboratory are precisely adjusted. When the actual temperature measured by the anti-microwave infrared temperature sensor is lower than the set temperature, the heating amount of the tubular heater is adjusted according to the temperature difference, and the unheated air passes through the air intake filter, the fan, the throttle valve to the backlog box, and is preheated by the 150W tubular heater, transported through the air intake guide groove, and then heated by the ceramic heater to blow the wind evenly on the diaphragm, thereby accurately controlling the diaphragm temperature.

[0017] As the preferred technical solution:

[0018] As described above, a method for preparing a polypropylene diaphragm with uniform air permeability and porosity, the heating and cooling backlog air knife also includes an adjusting handwheel, a touch screen, a control box and a pressure gauge, the adjusting handwheel is a worm gear mechanism, the worm is installed on the die head bracket, and is connected to the die head bracket by bolts, the turbine is fixed on the air outlet chamber, and is used to adjust the angle between the air outlet chamber and the casting roller; the touch screen is installed in the control box, mainly used to set the temperature and pressure, and the pressure gauge is installed in the backlog box, mainly used to monitor the pressure in the backlog box.

[0019] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity as described above, wherein the polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, wherein the middle layer is made of high melt index polypropylene, and the upper and lower layers are made of low melt index polypropylene;

[0020] The melt index (MI) of high melt index polypropylene measured at a temperature of 230°C and a load of 2.16 kg is 1.5~2.2 g / 10min, and the melt index of low melt index polypropylene measured at a temperature of 230°C and a load of 2.16 kg is 0.8~1.2 g / 10min.

[0021] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity as described above, wherein the thickness of the polypropylene diaphragm with uniform air permeability and porosity is 10~40μm, the thickness 2σ value is ≤0.2μm, the air permeability range is ≤100s / 100ml, the porosity range is ≤9%, the poor porosity ratio is ≤8%, the poor rate of vertical edges and ribs is ≤5%, and the higher the crystallinity, the better.

[0022] According to the method for preparing a polypropylene diaphragm with uniform air permeability and porosity, the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1.

[0023] In the method for preparing a polypropylene diaphragm with uniform air permeability and porosity as described above, the temperature of the extruder is 200-245° C., the surface temperature of the casting roller is 100-120° C., and the casting speed is 80-100 m / min.

[0024] The method for preparing a polypropylene diaphragm with uniform air permeability and porosity as described above comprises an annealing temperature of 120-155°C, an annealing time of 15-30 min, a cold drawing temperature of 30-100°C, and a cold drawing ratio of 1.05-1.30, a hot drawing temperature of 110-150°C, and a hot drawing ratio of 1.8-2.2, and forming process parameters of: a forming temperature of 130-160°C, a forming shrinkage ratio of 0.85-0.95, and a cooling temperature of 20-25°C.

[0025] Beneficial effects:

[0026] (1) The present invention provides a method for preparing a polypropylene diaphragm with uniform air permeability and porosity, wherein a heating and cooling backlog air knife is used to precisely control the temperature of the AK surface during the molding of the melt, and the AK surface and the CR surface can be crystallized synchronously, so that the polypropylene melt can reach the temperature range required for the lamellar structure when contacting the roller, and maintain the temperature until molding and can be cooled relatively slowly, thereby improving the crystallization behavior of the membrane to the greatest extent, so that the membrane has a parallel-arranged lamellar structure and is highly oriented, allowing the melt to crystallize under a higher stress field;

[0027] (2) The present invention provides a method for preparing a polypropylene diaphragm with uniform air permeability and porosity. The polypropylene base film is annealed at a certain temperature to obtain a hard elastic material having a lamellar structure perpendicular to the extrusion direction and arranged in parallel. The hard elastic material, as a highly oriented polymer, has the characteristics of high elasticity, high modulus, and low-temperature elasticity. A large number of micropores will appear when stretched, thereby ensuring the uniformity of the air permeability and porosity after stretching to the greatest extent. In the actual production process, the defective rate of vertical edges and exposed ribs is greatly reduced, thereby ensuring product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 , Figure 3 , Figure 4 A schematic diagram of a device used in a method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to the present invention;

[0029] Figure 2 Schematic diagram of the heating and cooling backlog air knife of the present invention, wherein the direction of the arrow is the direction of the airflow;

[0030] Figure 5 The process flow chart of the preparation method of a polypropylene diaphragm with uniform air permeability and porosity of the present invention;

[0031] Among them, 1-heating and cooling backlog air knife, 2-molten sheet, 3-cast film, 4-die, 5-self-exhaust pressure roller, 6-casting roller, 7-cooling roller, 8-adjusting hand wheel, 9-ceramic heater, 10-anti-microwave infrared temperature sensor, 11-touch screen, 12-inlet guide groove, 13-control box, 14-pressure gauge, 15-tubular heater, 16-air filter, 17-backlog box, 18-throttle valve, 19-fan, 20-servo motor, 21-inlet filter, 22-air outlet cavity, 23-die bracket. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0033] The test methods for the performance indicators involved in the embodiments and comparative examples of the present invention are as follows:

[0034] (1) Crystallinity:

[0035] Tools: Differential Scanning Calorimeter (DSC), model: Q2000, manufacturer: TA Company, USA;

[0036] Method: DSC thermal enthalpy method, according to the processing temperature range (180℃~250℃) provided by the raw material manufacturer, the hot melting value of the sample crystal is determined by dividing it by the hot melting value of 100% crystal:

[0037]

[0038] in: is the crystallinity, is the measured lamellar melting value, It is 100% lamellar hot melting value;

[0039] (2) Porosity: Tested in accordance with GB / T 36363-2018;

[0040] Tools: ① Sampling plate (self-made) 100mm*100mm, accuracy ±0.01mm;

[0041] ②Mahl thickness gauge, model: C1208;

[0042] ③Ohaus electronic balance, model: AR323CN;

[0043] Method: Take a polypropylene diaphragm with a longitudinal (MD) length of 1500mm, and fold it evenly every 300mm along the MD direction for 4 times; use a sampling plate to sample in sequence along the transverse direction of the diaphragm. The polypropylene diaphragm is 1200mm wide. The starting position to the end position is the sequence of equidistant die head bolts 1 to 57. Sampling begins at 50mm from the edge. Each layer has 11 samples, a total of 5 layers. Take 5 points from each layer to measure the thickness with a Marr thickness gauge. Take the average value of the 5 points as the thickness value of each sample (i.e., polypropylene diaphragm). Turn on the balance power supply, wait for the balance to be standardized and zeroed, open the side door of the balance, put the sample with measured thickness into the balance, measure its mass, and the surface density calculation formula is:

[0044] ρ 1= ;

[0045] Where: 1 ——Surface density of the diaphragm, in grams per square centimeter (g / cm 2 );

[0046] m——mass of the diaphragm, in grams (g);

[0047] ——The length of the diaphragm, in cm;

[0048] b——the width of the diaphragm, in cm;

[0049] Then use the formula: Calculate porosity;

[0050] Among them, ρ 1 ——Surface density of the diaphragm, in grams per square centimeter (g / cm 2 );

[0051] p——Porosity of the diaphragm, unit is %;

[0052] d——the thickness of the diaphragm, in micrometers (μm);

[0053] ρ 0 ——Density of the diaphragm material, in grams per square centimeter (g / cm 2 );

[0054] Porosity range: The maximum porosity of each layer minus the minimum porosity of the layer is called the porosity range;

[0055] Porosity ratio: refers to the percentage of the number of porosity values ​​exceeding the standard range in a layer of diaphragm divided by the total number of measurements in the layer; the calculation formula is as follows:

[0056] ;

[0057] in: ——Poor porosity ratio of the layer;

[0058] ——The number of porosity values ​​of the layer exceeding the standard;

[0059] ——The total number of porosity values ​​measured for this layer.

[0060] (3) Air permeability:

[0061] Instrument: Asahi Seiko Air Permeability Tester Model: EG01-55-1MR;

[0062] Sampling method: Take a polypropylene diaphragm with a longitudinal (MD) length of 1500mm, fold it back and forth evenly every 300mm in the MD direction, fold it 4 times, the width of the polypropylene diaphragm is 1200mm, the starting position to the end position is the sequence of the die head bolts 1-57, and the measurement starts at 50mm from the edge. On the polypropylene diaphragm, along the TD (transverse) direction and corresponding to the sequence of bolts 1-57, measure the air permeability value of one point every 100mm (the air permeability value is not measured within 50mm on both sides), record the air permeability value of each point, and perform air permeability control at a single point;

[0063] Range: The maximum air permeability value of each layer minus the minimum air permeability value of that layer is called the range.

[0064] (4) Defective rate of vertical edge reinforcement:

[0065] (4.1) Vertical edge:

[0066] Tools: Appearance test car (self-made with reference to CN 202529011U);

[0067] Standard weight: 50g×2;

[0068] Method: Take a diaphragm with a length of 1000mm in the MD direction and place it on the appearance test trolley. One side in the MD direction is placed on the roller at the fixed end of the appearance test trolley, and the other side is fixed on the movable side of the carbon fiber rod with a weight of 100g. Hang 50g weights on both sides of the carbon fiber rod respectively, and visually inspect whether there is edge collapse on both sides. If the overall consistency and no obvious edge collapse on both sides are qualified products, if the edge has an edge collapse of ≥3mm, it is a failed product.

[0069] (4.2) Tendon tension:

[0070] Tools: inspection trolley, soft light 600lm, dust-free gloves;

[0071] Method: Use the lithium battery diaphragm integrated slitting machine produced by Nanjing Jiaxu, model: SLL21B, to slit the film roll at an interval of 61mm in the vertical extrusion direction. Place the slit film roll on the test trolley and visually check whether there are longitudinal stripes on the surface of the film roll. If there are no longitudinal stripes, it is a qualified product. If there are, it is judged whether it is bottom wrinkles. Wear dust-free gloves and touch the surface of the film roll to see if there are hard stripes. If there are no hard stripes, it is a qualified product. If there are hard stripes, it is a failed product.

[0072] Calculation method: Defective rate of vertical edge ribs = number of vertical edge ribs / total number of inspections*100%.

[0073] (5) Melt index MI: Tested with reference to GBT3682-2000, PP was tested at a temperature of 230°C, a load of 2.16 kg, and an inner diameter of the capillary die of 2.096 mm.

[0074] (6) Thickness 2σ value: σ is the standard deviation, 2σ is 2 standard deviations, and the standard deviation is the arithmetic square root of the arithmetic mean of the sum of squares of the deviations from the mean, that is, the arithmetic square root of the variance, represented by σ. The standard deviation is also called the standard deviation, or the experimental standard deviation, and is most commonly used in probability statistics as a measure of the degree of statistical distribution. The standard deviation can reflect the degree of dispersion of a data set. Two sets of data with the same mean may not have the same standard deviation.

[0075] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity, such as Figure 1 , Figure 3 , Figure 4 As shown, it includes a heating and cooling backlog air knife 1, a die head 4, a self-exhaust pressure roller 5, a casting roller 6 and a cooling roller 7;

[0076] like Figure 2 As shown, the heating and cooling backlog air knife 1 includes a ceramic heater 9, an anti-microwave infrared temperature sensor 10, an air inlet guide groove 12, a tubular heater 15, an air filter 16, a backlog box 17, a throttle valve 18, a fan 19, a servo motor 20, an air inlet filter 21, an air outlet cavity 22, an adjustment hand wheel 8, a touch screen 11, a control box 13 and a pressure gauge 14;

[0077] The air outlet cavity 22 is a hollow structure with one end sealed and the other end open; the interior of the air outlet cavity 22 includes a flow guiding section and a non-flow guiding section; the flow guiding section is close to the sealed end of the air outlet cavity 22 and is a vortex structure; the non-flow guiding section is far away from the sealed end of the air outlet cavity 22, and the ceramic heater 9 is arranged on the non-flow guiding section;

[0078] Above the die head 4 is a die head bracket 23, and both sides of the air outlet cavity 22 are installed on the die head bracket 23; the inner cavity of the air intake filter 21 is connected to the air inlet of the fan 19, and the fan 19 is connected to the servo motor 20. The size of the air intake is adjusted by controlling the speed of the servo motor. The fan 19 is also connected to the backlog box 17 through a pipeline, and a throttle valve 18 is arranged on the pipeline; the backlog box 17 is connected to the air filter 16 and the tubular heater 15 in sequence, and the tubular heater 15 is connected to the guide section through the air intake guide groove 12; the connection between the air intake guide groove 12 and the guide section is set as the air inlet, the open end of the air outlet cavity 22 is the air outlet, and the microwave-resistant infrared temperature sensor 10 is installed at the air outlet;

[0079] The adjusting hand wheel 8 is a worm gear mechanism, the worm is installed on the die head bracket 23 and connected to the die head bracket 23 by bolts, and the turbine is fixed on the air outlet cavity 22; the touch screen 11 is installed in the control box 13, and the pressure gauge 14 is installed in the backlog box 17.

[0080] Specific usage process: the molten sheet 2 flows out from the die head 4 to the casting roller 6, the heating and cooling backlog air knife 1 is in a non-contact state with the casting roller 6, and the temperature is accurately measured by the anti-microwave infrared temperature sensor 10. According to the temperature comparison result, the ceramic heater 9 and the tubular heater 15 are started / stopped respectively. At the same time, the casting roller 6 cooperates with the heating and cooling backlog air knife 1 to slowly cool the molten sheet 2 (hereinafter referred to as the membrane). The self-exhaust pressure roller 5 is installed under the casting roller 6, and the membrane is passed between the self-exhaust pressure roller 5 and the casting roller 6. After the membrane is flat, it is pressed on the self-exhaust pressure roller 5 and then passed through the cooling roller 7 to obtain a polypropylene base film (i.e., the casting film 3). The polypropylene base film is successively cold-drawn, hot-drawn, and shaped to obtain a polypropylene diaphragm with uniform air permeability and porosity.

[0081] When the heating and cooling backlog air knife 1 is started, the servo motor 20 is powered on, and the condition of the molten sheet 2 is observed at the same time (standard: no surface defects such as holes are visually observed, and the edges are consistent), the distance and angle of the air outlet cavity 22 are adjusted, and then the temperature is adjusted according to the actual temperature measured by the anti-microwave infrared temperature sensor 10 on the molten sheet 2 (the set temperature satisfies 131°C≤T≤138°C, which is synchronized with the actual temperature), and then the air permeability value, porosity and other indicators measured in the laboratory are accurately adjusted. When the actual temperature measured by the anti-microwave infrared temperature sensor 10 is lower than the set temperature, the heating amount of the tubular heater 15 is adjusted according to the temperature difference, and the unheated air passes through the air intake filter 21, the fan 19, the throttle valve 18 to the backlog box 17, and is preheated by the 150W tubular heater 15, and is transported to the guide section through the air intake guide groove 12, and then the wind is blown evenly on the diaphragm through the ceramic heater 9, thereby accurately controlling the diaphragm temperature.

[0082] Example 1

[0083] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity, the specific steps are as follows:

[0084] (1) Preparation of raw materials:

[0085] Middle layer material: low melt index polypropylene, manufacturer: TPC, brand: FS2014, the melt index of low melt index polypropylene measured at a temperature of 230°C and a load of 2.16kg is 0.8g / 10min;

[0086] The upper and lower layer materials are: high melt index polypropylene, which is a mixture of polypropylene (manufacturer: TPC, brand: FS1014) and polypropylene (manufacturer: TPC, brand: SF232) in a molar ratio of 1:1. The melt index of the high melt index polypropylene measured at a temperature of 230°C and a load of 2.16 kg is 1.8 g / 10 min.

[0087] (2) If Figure 5 As shown, the middle layer raw material is fed into the main extruder A, and the upper and lower layer raw materials are respectively fed into the auxiliary extruder B, and a polypropylene melt is obtained after melting and plasticizing. The polypropylene melt is extruded from the die head to form a molten sheet, and a heating and cooling backlog air knife is used to accurately control the molten sheet to enter the casting roller for casting molding at a temperature of 135°C and an air pressure of 0.25MPa, and then the polypropylene base film is obtained by passing through a self-exhaust pressure roller and a cooling roller in sequence. The polypropylene base film is successively annealed, cold drawn, hot drawn, and shaped to obtain a polypropylene diaphragm with uniform air permeability and porosity;

[0088] Among them, the temperatures of the first, second and third zones of the main extruder A are 215°C, 240°C and 235°C respectively; the temperatures of the first, second and third zones of the auxiliary extruder B are 213°C, 238°C and 232°C respectively; the temperature of the die head is 225°C, the surface temperature of the casting roller is 100°C, and the casting speed is 100m / min; the annealing temperature is 135°C, and the annealing time is 15min; the cold stretching temperature is 80°C, and the cold stretching ratio is 1.15; the hot stretching temperature is 140°C, and the hot stretching ratio is 1.9; the process parameters for shaping are: shaping temperature 155°C, shaping retraction ratio 0.95, shaping time 10min; cooling temperature 25°C; target thickness is 18μm.

[0089] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the thickness of the polypropylene diaphragm with uniform air permeability and porosity is 18μm, the thickness 2σ value is 0.13μm, the crystallinity is 50.8%, the extreme difference of air permeability is 61s / 100ml, the extreme difference of porosity is 6%, the proportion of poor porosity is 3.5%, and the poor rate of vertical edge ribs is 3.3%.

[0090] Comparative Example 1

[0091] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that the heating, cooling and backlog air knife are turned off.

[0092] The thickness of the prepared polypropylene diaphragm is 18.00μm, the thickness 2σ value is 0.23μm, the crystallinity is 47.2%, the extreme value of air permeability is 133s / 100ml, the extreme value of porosity is 18%, the proportion of poor porosity is 17.65%, and the defective rate of vertical edge ribs is 10.3%.

[0093] Comparative Example 2

[0094] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0095] The thickness of the prepared polypropylene diaphragm is 18.01μm, the thickness 2σ value is 0.17μm, the crystallinity is 49.7%, the extreme value of air permeability is 91s / 100ml, the extreme value of porosity is 13%, the proportion of poor porosity is 4.71%, and the defective rate of vertical edge ribs is 6.3%.

[0096] Comparative Example 3

[0097] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0098] The thickness of the prepared polypropylene diaphragm is 18.01 μm, the thickness 2σ value is 0.22 μm, the crystallinity is 48.6%, the extreme value of air permeability is 109 s / 100 ml, the extreme value of porosity is 11%, the proportion of poor porosity is 8.25%, and the defective rate of vertical edge ribs is 5.4%.

[0099] Comparative Example 4

[0100] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0101] The thickness of the prepared polypropylene diaphragm is 18.02μm, the thickness 2σ value is 0.18μm, the crystallinity is 48.7%, the extreme value of air permeability is 95s / 100ml, the extreme value of porosity is 9%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 5.2%.

[0102] By comparing Example 1 with Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, it can be found that when the target thickness is 18 μm, when the temperature of the heating and cooling backlog air knife in Example 1 is controlled within the range of 131-138°C, the measured values ​​of the thickness 2σ value, crystallinity, air permeability extreme difference, porosity extreme difference, poor porosity ratio, and vertical edge rib defect rate are all better than those of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. This is because after the heating and cooling backlog air knife is started and the temperature is accurately controlled within the range of 131-138°C by using the heating and cooling backlog air knife, the back side of the diaphragm is heated to the ambient temperature required for the growth of the lamellae by the device and controlled within the range of 131-138°C. , making the crystallization more regular and the direction more consistent, and the defects perpendicular to the extrusion direction are arranged more evenly when the silver streaks are cold stretched, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as air permeability and porosity uniformity are improved, and the defect rate of related performance of the product is reduced. Therefore, by heating and cooling the backlog air knife and accurately controlling the temperature at 131~138℃, its thickness is closer to the set value, and its 2σ value is closer to 0. The measured values ​​of crystallinity, extreme air permeability, extreme porosity, poor porosity ratio, and vertical edge rib defect rate are better than those without heating and cooling backlog air knife or the heating and cooling backlog air knife temperature is not controlled at 131~138℃.

[0103] Example 2

[0104] A method for producing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as in Example 1, except that:

[0105] The temperatures of the first, second and third zones of the main extruder A are 212°C, 238°C and 232°C respectively; the temperatures of the first, second and third zones of the auxiliary extruder B are 215°C, 235°C and 230°C respectively; the annealing time is 18min; the cold stretching temperature is 82°C, and the cold stretching ratio is 1.16; the hot stretching temperature is 145°C, and the hot stretching ratio is 2.0; the shaping process parameters are: shaping temperature 156°C, shaping retraction ratio 0.90; the target thickness is 20μm.

[0106] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the polypropylene diaphragm with uniform air permeability and porosity has a membrane thickness of 20μm, a thickness 2σ value of 0.14μm, a crystallinity of 50.5%, an air permeability range of 69s / 100ml, a porosity range of 7%, a poor porosity ratio of 4.71%, and a poor rate of vertical edge ribs of 4.3%.

[0107] Comparative Example 5

[0108] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 2, except that the heating, cooling and backlog air knife are turned off.

[0109] The thickness of the prepared polypropylene diaphragm is 20.04μm, the thickness 2σ value is 0.26μm, the crystallinity is 47.4%, the extreme value of air permeability is 141s / 100ml, the extreme value of porosity is 21%, the proportion of poor porosity is 21.18%, and the defective rate of vertical edge ribs is 12.6%.

[0110] Comparative Example 6

[0111] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 2, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0112] The thickness of the prepared polypropylene diaphragm is 19.98μm, the thickness 2σ value is 0.18μm, the crystallinity is 48.3%, the extreme value of air permeability is 91s / 100ml, the extreme value of porosity is 10%, the proportion of poor porosity is 8.24%, and the defective rate of vertical edge ribs is 6.1%.

[0113] Comparative Example 7

[0114] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 2, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0115] The thickness of the prepared polypropylene diaphragm is 20.01 μm, the thickness 2σ value is 0.17 μm, the crystallinity is 49.5%, the extreme value of air permeability is 97s / 100ml, the extreme value of porosity is 13.7%, the proportion of poor porosity is 5.89%, and the defective rate of vertical edge ribs is 5.5%.

[0116] Comparative Example 8

[0117] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 2, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0118] The thickness of the prepared polypropylene diaphragm is 20.03μm, the thickness 2σ value is 0.19μm, the crystallinity is 50.2%, the extreme value of air permeability is 89s / 100ml, the extreme value of porosity is 12%, the proportion of poor porosity is 9.41%, and the defective rate of vertical edge ribs is 8.6%.

[0119] By comparing Example 2 with Comparative Examples 5, 6, 7 and 8, it can be found that when the target thickness is 20 μm, when the temperature of the heating and cooling backlog air knife in Example 2 is controlled within the range of 131°C to 138°C, the measured values ​​of the 2σ value of the thickness, the degree of crystallinity, the extreme difference in air permeability, the extreme difference in porosity, the proportion of poor porosity and the poor rate of vertical edge ribs are all better than those of Comparative Examples 5, 6, 7 and 8. This is because after the heating and cooling backlog air knife is started and the temperature of the heating and cooling backlog air knife is controlled within the range of 131°C to 138°C, the back side of the diaphragm is heated to the ambient temperature (131°C to 138°C) required for the growth of the lamellar crystals by the device, so that the crystallization is more regular, and the defects perpendicular to the extrusion direction are arranged more evenly when the silver streaks are cold stretched, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as the air permeability and porosity uniformity are improved, and the defect rate of the relevant performance of the product is reduced.

[0120] Example 3

[0121] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that:

[0122] The temperatures of the first, second and third zones of the main extruder A are 213°C, 238°C and 233°C respectively; the temperatures of the first, second and third zones of the auxiliary extruder B are 210°C, 235°C and 230°C respectively; the cold stretching temperature is 78°C, the hot stretching temperature is 138°C, and the setting temperature is 153°C; the target thickness is 12μm.

[0123] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the polypropylene diaphragm with uniform air permeability and porosity has a membrane thickness of 12.00μm, a thickness 2σ value of 0.09μm, a crystallinity of 51.2%, an air permeability range of 47s / 100ml, a porosity range of 5%, a poor porosity ratio of 3.53%, and a poor rate of vertical edge ribs of 4.9%.

[0124] Comparative Example 9

[0125] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 3, except that the heating, cooling and backlog air knife are turned off.

[0126] The thickness of the prepared polypropylene diaphragm is 12.03μm, the thickness 2σ value is 0.19μm, the crystallinity is 48.6%, the extreme value of air permeability is 112s / 100ml, the extreme value of porosity is 17%, the proportion of poor porosity is 9.41%, and the defective rate of vertical edge ribs is 11.7%.

[0127] Comparative Example 10

[0128] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 3, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0129] The thickness of the prepared polypropylene diaphragm is 12.00μm, the thickness 2σ value is 0.15μm, the crystallinity is 49.2%, the extreme value of air permeability is 77s / 100ml, the extreme value of porosity is 9%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 6.6%.

[0130] Comparative Example 11

[0131] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 3, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0132] The thickness of the prepared polypropylene diaphragm is 12.01μm, the thickness 2σ value is 0.13μm, the crystallinity is 49.7%, the extreme value of air permeability is 68s / 100ml, the extreme value of porosity is 10%, the proportion of poor porosity is 5.89%, and the defective rate of vertical edge ribs is 5.3%.

[0133] Comparative Example 12

[0134] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 3, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0135] The thickness of the prepared polypropylene diaphragm is 12.03μm, the thickness 2σ value is 0.17μm, the crystallinity is 50.1%, the extreme value of air permeability is 79s / 100ml, the extreme value of porosity is 12%, the proportion of poor porosity is 8.25%, and the defective rate of vertical edge ribs is 6.7%.

[0136] By comparing Example 3 with Comparative Examples 9, 10, 11 and 12, it can be found that when the target thickness is 12 μm, when the temperature of the heating and cooling backlog air knife in Example 3 is controlled in the range of 131°C to 138°C, the measured values ​​of the 2σ value of the thickness, the degree of crystallinity, the extreme difference in air permeability, the extreme difference in porosity, the proportion of poor porosity and the poor rate of vertical edge ribs are all better than those of Comparative Examples 9, 10, 11 and 12. This is because after the heating and cooling backlog air knife is started and the temperature of the heating and cooling backlog air knife is controlled in the range of 131°C to 138°C, the back side of the diaphragm is heated to the ambient temperature (131°C to 138°C) required for the growth of the lamellae by the device, so that the crystallization is more regular, and the defects perpendicular to the extrusion direction are arranged more evenly when the silver streaks are cold stretched, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as the air permeability and porosity uniformity are improved, and the defective rate of the relevant performance of the product is reduced.

[0137] Example 4

[0138] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 1, except that:

[0139] The temperatures of the first, second and third zones of the main extruder A are 212°C, 238°C and 232°C respectively; the temperatures of the first, second and third zones of the auxiliary extruder B are 210°C, 235°C and 230°C respectively; the annealing time is 13min; the cold stretching temperature is 75°C, and the cold stretching ratio is 1.15; the hot stretching temperature is 135°C, and the hot stretching ratio is 1.9; the forming process parameters are: forming temperature 150°C, and the target thickness is 10μm.

[0140] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the polypropylene diaphragm with uniform air permeability and porosity has a membrane thickness of 10.00μm, a thickness 2σ value of 0.09μm, a crystallinity of 51.2%, an air permeability range of 43s / 100ml, a porosity range of 5%, a poor porosity ratio of 3.53%, and a poor rate of vertical edge ribs of 3.7%.

[0141] Comparative Example 13

[0142] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 4, except that the heating, cooling and backlog air knife are turned off.

[0143] The thickness of the prepared polypropylene diaphragm is 10.04μm, the thickness 2σ value is 0.18μm, the crystallinity is 48.6%, the extreme value of air permeability is 102s / 100ml, the extreme value of porosity is 15%, the proportion of poor porosity is 11.76%, and the defective rate of vertical edge ribs is 9.1%.

[0144] Comparative Example 14

[0145] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 4, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0146] The thickness of the prepared polypropylene diaphragm is 9.97μm, the thickness 2σ value is 0.14μm, the crystallinity is 49.2%, the extreme value of air permeability is 71s / 100ml, the extreme value of porosity is 10%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 5.3%.

[0147] Comparative Example 15

[0148] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 4, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0149] The thickness of the prepared polypropylene diaphragm is 9.90μm, the thickness 2σ value is 0.14μm, the crystallinity is 49.6%, the extreme value of air permeability is 59s / 100ml, the extreme value of porosity is 9%, the proportion of poor porosity is 5.89%, and the defective rate of vertical edge ribs is 4.8%.

[0150] Comparative Example 16

[0151] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 4, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0152] The thickness of the prepared polypropylene diaphragm is 10.02μm, the thickness 2σ value is 0.15μm, the crystallinity is 50.5%, the extreme value of air permeability is 81s / 100ml, the extreme value of porosity is 11%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 5.4%.

[0153] By comparing Example 4 with Comparative Examples 13, 14, 15 and 16, it can be found that when the target thickness is 10 μm, when the temperature of the heating and cooling backlog air knife in Example 4 is controlled within the range of 131°C to 138°C, the measured values ​​of the 2σ value of the thickness, crystallinity, extreme difference in air permeability, extreme difference in porosity, proportion of poor porosity and poor rate of vertical edge ribs are all better than those of Comparative Examples 13, 14, 15 and 16. This is because after the heating and cooling backlog air knife is started and the temperature of the heating and cooling backlog air knife is controlled within the range of 131°C to 138°C, the back side of the diaphragm is heated to the ambient temperature (131°C to 138°C) required for the growth of the lamellar crystals by the device, so that the crystallization is more regular, and the defects perpendicular to the extrusion direction are arranged more evenly during the cold-stretching of the silver streaks, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as air permeability and porosity uniformity are improved, and the defect rate of related performance of the product is reduced.

[0154] Example 5

[0155] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 1, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 131° C., and the target thickness is 32 μm.

[0156] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the thickness of the polypropylene diaphragm with uniform air permeability and porosity is 32.01μm, the thickness 2σ value is 0.16μm, the crystallinity is 50.5%, the extreme difference of air permeability is 71s / 100ml, the extreme difference of porosity is 8%, the proportion of poor porosity is 5.89%, and the poor rate of vertical edge ribs is 4.6%.

[0157] Comparative Example 17

[0158] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 5, except that the heating, cooling and backlog air knife are turned off.

[0159] The thickness of the prepared polypropylene diaphragm is 32.12μm, the thickness 2σ value is 0.26μm, the crystallinity is 44.8%, the extreme value of air permeability is 141s / 100ml, the extreme value of porosity is 25%, the proportion of poor porosity is 24.71%, and the defective rate of vertical edge ribs is 13.5%.

[0160] Comparative Example 18

[0161] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that in Example 5, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0162] The thickness of the prepared polypropylene diaphragm is 32.08μm, the thickness 2σ value is 0.19μm, the crystallinity is 48.6%, the extreme value of air permeability is 90s / 100ml, the extreme value of porosity is 13%, the proportion of poor porosity is 10.59%, and the defective rate of vertical edge ribs is 7.0%.

[0163] Comparative Example 19

[0164] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 5, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0165] The thickness of the prepared polypropylene diaphragm is 32.05μm, the thickness 2σ value is 0.17μm, the crystallinity is 49.4%, the extreme value of air permeability is 81s / 100ml, the extreme value of porosity is 10%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 5.8%.

[0166] Comparative Example 20

[0167] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as that of Example 5, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0168] The thickness of the prepared polypropylene diaphragm is 32.11μm, the thickness 2σ value is 0.21μm, the crystallinity is 49.2%, the extreme value of air permeability is 101s / 100ml, the extreme value of porosity is 19%, the proportion of poor porosity is 12.94%, and the defective rate of vertical edge ribs is 8.1%.

[0169] By comparing Example 5 with Comparative Examples 17, 18, 19 and 20, it can be found that when the target thickness is 32 μm, when the temperature of the heating and cooling backlog air knife in Example 5 is controlled within the range of 131°C to 138°C, the measured values ​​of the 2σ value of the thickness, the degree of crystallinity, the extreme difference in air permeability, the extreme difference in porosity, the proportion of poor porosity and the poor rate of vertical edge ribs are all better than those of Comparative Examples 17, 18, 19 and 20. This is because after the heating and cooling backlog air knife is started and the temperature of the heating and cooling backlog air knife is controlled within the range of 131°C to 138°C, the back side of the diaphragm is heated to the ambient temperature (131°C to 138°C) required for the growth of the lamellae by the device, so that the crystallization is more regular, and the defects perpendicular to the extrusion direction are arranged more evenly during the cold-stretching of the silver streaks, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as the air permeability and porosity uniformity are improved, and the defective rate of the relevant performance of the product is reduced.

[0170] Example 6

[0171] A method for producing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as in Example 1, except that:

[0172] The temperatures of the first, second and third zones of the main extruder A are 212°C, 238°C and 232°C respectively; the temperatures of the first, second and third zones of the auxiliary extruder B are 210°C, 235°C and 230°C respectively; the annealing time is 18min; the cold stretching temperature is 82°C, and the cold stretching ratio is 1.16; the hot stretching temperature is 145°C, and the hot stretching ratio is 2.0; the process parameters for shaping are: shaping temperature 156°C, high temperature shaping retraction ratio 0.90, and target thickness: 40μm.

[0173] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the thickness of the polypropylene diaphragm with uniform air permeability and porosity is 40μm, the thickness 2σ value is 0.15μm, the crystallinity is 50.5%, the extreme difference of air permeability is 81s / 100ml, the extreme difference of porosity is 8%, the proportion of poor porosity is 5.89%, and the poor rate of vertical edge ribs is 4.8%.

[0174] Comparative Example 21

[0175] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 6, except that the heating, cooling and backlog air knife are turned off.

[0176] The thickness of the prepared polypropylene diaphragm is 39.96μm, the thickness 2σ value is 0.25μm, the crystallinity is 45.2%, the extreme value of air permeability is 171s / 100ml, the extreme value of porosity is 27%, the proportion of poor porosity is 24.71%, and the defective rate of vertical edge ribs is 15.1%.

[0177] Comparative Example 22

[0178] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 6, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 120°C.

[0179] The thickness of the prepared polypropylene diaphragm is 39.97μm, the thickness 2σ value is 0.19μm, the crystallinity is 48.4%, the extreme value of air permeability is 97s / 100ml, the extreme value of porosity is 16%, the proportion of poor porosity is 11.76%, and the defective rate of vertical edge ribs is 6.9%.

[0180] Comparative Example 23

[0181] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 6, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 130°C.

[0182] The thickness of the prepared polypropylene diaphragm is 39.97μm, the thickness 2σ value is 0.17μm, the crystallinity is 49.4%, the extreme value of air permeability is 89s / 100ml, the extreme value of porosity is 11%, the proportion of poor porosity is 7.06%, and the defective rate of vertical edge ribs is 5.5%.

[0183] Comparative Example 24

[0184] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 6, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 140°C.

[0185] The thickness of the prepared polypropylene diaphragm is 39.93μm, the thickness 2σ value is 0.20μm, the crystallinity is 50.1%, the extreme value of air permeability is 102s / 100ml, the extreme value of porosity is 18%, the proportion of poor porosity is 14.11%, and the defective rate of vertical edge ribs is 9.6%.

[0186] By comparing Example 6 with Comparative Examples 21, 22, 23 and 24, it can be found that when the target thickness is 10 μm, when the temperature of the heating and cooling backlog air knife in Example 6 is controlled within the range of 131°C to 138°C, the measured values ​​of thickness 2σ value, crystallinity, air permeability extreme value, porosity extreme value, poor porosity ratio and vertical edge rib defect rate are all better than those of Comparative Examples 21, 22, 23 and 24. This is because after the heating and cooling backlog air knife is started and the temperature of the heating and cooling backlog air knife is controlled within the range of 131°C to 138°C, the back side of the diaphragm is heated to the ambient temperature (131°C to 138°C) required for the growth of the lamellae through the device, so that the crystallization is more regular, and the defects perpendicular to the extrusion direction are arranged more evenly during the cold-stretching silver streaks, thereby greatly improving the uniformity of the micropores generated by the defects. Therefore, important indicators such as air permeability and porosity uniformity are improved, and the defect rate of related performance of the product is reduced.

[0187] Example 7

[0188] A method for preparing a polypropylene diaphragm with uniform air permeability and porosity is basically the same as Example 1, except that a heating and cooling backlog air knife accurately controls the temperature of the molten sheet at 138° C., and the target thickness is 16 μm.

[0189] The final polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, and the thickness ratio of the upper, middle and lower layers of the polypropylene diaphragm with uniform air permeability and porosity is 1:3:1; the thickness of the polypropylene diaphragm with uniform air permeability and porosity is 16.01μm, the thickness 2σ value is 0.14μm, the crystallinity is 50.2%, the extreme difference of air permeability is 81s / 100ml, the extreme difference of porosity is 9%, the proportion of poor porosity is 5.41%, and the poor rate of vertical edge ribs is 4.1%.

[0190] Based on the above embodiments and comparative examples, when the heating and cooling backlog air knife is turned on and the temperature is controlled within (131°C~138°C), the physical properties of the obtained diaphragm are all within the control indicators, which is better than not turning on the heating and cooling backlog air knife or not controlling the temperature within (131°C~138°C). Therefore, adding a heating and cooling backlog air knife during molding and controlling the temperature within (131°C~138°C) can make the physical properties of the diaphragm closer to the set values, greatly improving the uniformity of physical properties such as air permeability and porosity.

Claims

1. A method for preparing a polypropylene diaphragm with uniform air permeability and porosity, characterized in that: The polypropylene is melted and plasticized by an extruder to obtain a polypropylene melt, which is extruded from a die head (4) to form a molten sheet. The molten sheet is controlled at a temperature of 131 to 138° C. and then enters a casting roller (6) for casting. The molten sheet then passes through a self-exhausting pressure roller (5) and a cooling roller (7) in sequence to obtain a polypropylene base film. The polypropylene base film is sequentially subjected to annealing treatment, cold drawing, hot drawing, and shaping to obtain a polypropylene diaphragm with uniform air permeability and porosity. The temperature of the molten sheet is precisely controlled to 131-138°C by using a heating and cooling compressed air knife (1); The heating and cooling backlog air knife comprises a ceramic heater (9), an anti-microwave infrared temperature sensor (10), an air inlet guide groove (12), a tubular heater (15), an air filter (16), a backlog box (17), a throttle valve (18), a fan (19), a servo motor (20), an air inlet filter (21) and an air outlet chamber (22); The air outlet cavity (22) is a hollow structure with one end sealed and the other end open; the interior of the air outlet cavity (22) includes a flow guiding section and a non-flow guiding section; The flow-guiding section is close to the sealed end of the air outlet cavity and is a vortex-shaped structure; the non-flow-guiding section is far from the sealed end of the air outlet cavity, and the ceramic heater (9) is arranged on the non-flow-guiding section; A die head bracket (23) is disposed above the die head (4), and two sides of the air outlet chamber (22) are mounted on the die head bracket (23); the inner cavity of the air intake filter (21) is connected to the air intake of the fan (19), the fan (19) is connected to the servo motor (20), and the air intake volume is adjusted by controlling the speed of the servo motor (20); the fan (19) is also connected to the accumulation box (17) through a pipeline, and a throttle valve (18) is arranged on the pipeline; the accumulation box (17) is connected to the air filter (16) and the tubular heater (15) in sequence, and the tubular heater (15) is connected to the guide section through the air intake guide groove (12); the connection between the air intake guide groove (12) and the guide section is set as the air intake, the open end of the air outlet chamber is set as the air outlet, and the microwave-resistant infrared temperature sensor (10) is mounted at the air outlet.

2. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 1, characterized in that: The heating, cooling and backlog air knife also includes an adjusting hand wheel (8), a touch screen (11), a control box (13) and a pressure gauge (14); the adjusting hand wheel (8) is a worm gear mechanism; the worm gear is mounted on a die head bracket and connected to the die head bracket by bolts; the turbine is fixed on an air outlet cavity (22); the touch screen (11) is mounted in the control box (13), and the pressure gauge (14) is mounted in the backlog box (17).

3. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 2, characterized in that: The polypropylene diaphragm with uniform air permeability and porosity is a three-layer composite structure, the middle layer is made of low melt index polypropylene, and the upper and lower layers are made of high melt index polypropylene; The melt index of high melt index polypropylene measured at a temperature of 230°C and a load of 2.16 kg is 1.5~2.2 g / 10min, and the melt index of low melt index polypropylene measured at a temperature of 230°C and a load of 2.16 kg is 0.8~1.2 g / 10min.

4. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 3, characterized in that: The thickness of the polypropylene diaphragm with uniform air permeability and porosity is 10~40μm, the thickness 2σ value is ≤0.2μm, the air permeability range is ≤100s / 100ml, and the porosity range is ≤9%.

5. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 4, characterized in that: The thickness ratio of the upper, middle and lower layers of the polypropylene separator with uniform air permeability and porosity is 1:3:

1.

6. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 1, characterized in that: The temperature of the extruder is 200~245℃, the surface temperature of the casting roller is 100~120℃, and the casting speed is 80~100m / min.

7. The method for preparing a polypropylene diaphragm with uniform air permeability and porosity according to claim 5, characterized in that: The annealing temperature is 120~155℃, and the annealing time is 15~30min; the cold drawing temperature is 30~100℃, and the cold drawing ratio is 1.05~1.30; the hot drawing temperature is 110~150℃, and the hot drawing ratio is 1.8~2.2; the forming process parameters are: forming temperature 130~160℃, forming shrinkage ratio 0.85~0.95, and cooling temperature 20~25℃.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm and preparation method thereof

    CN102376928A

  • Anti-static trolley special for membrane

    CN202529011U

  • Preparation method of polyolefin microporous membrane

    CN106626457A

  • Preparation method of battery diaphragm, battery diaphragm and tape casting cooling device

    CN116598702A

  • Photosensitive dry film protective film and production equipment thereof

    CN117261388A